Non destructive tests for railway infrastructure stiffness evaluation - Fontul, S. (2011)
An important part for a proper railway maintenance policy is the evaluation of the condition of an existing railway substructure, in order to detect the deterioration causes. Recently, the use of non destructive techniques for substructure evaluation has increased due to advantages that these monitoring methods present. Several non destructive tests, loading tests and thickness measurement, were performed on a track section, part of a new railway line designed for high speed traffic. This paper presents the results achieved so far, the testing methodologies defined and the main concerns regarding the use of non destructive tests on a railway platform.